Gaya Hidup Remaja dan Penggunaan Telepon Seluler di Kota Medan - Elida Usni; Harmona Daulay; Ria Manurung; Rizabuana Ismail; Henry Sitorus (Universitas Negeri Medan, 2019)
Mobile phones for teenagers turn out to be used more than just a means of ordinary communication, cell phone use in teenagers' daily lives related to lifestyle. The purpose of this study is to find out cell phone use for teenagers. This method was chosen because the issue that was explored was a matter of meaning. Data collection techniques used included observation and interviews. Mobile phones are used as an image of the lifestyle of teenagers buying a mobile phone that is trending with the main reason to look slang, have confidence in front of their friends, and show who they are to others. Mobile phones are very important items in the lives of teenagers. Innovations that are presented in the features available on mobile phones make teenagers increasingly unable to escape from this one object. Based on the results of the study, it can be concluded that cell phone phones are important in teenager’s life; mobile phones are a side of modern life, cell phones as a lifestyle obtained in cell phones when used.